Evaluation of the dry eye disease parameters with exposure to dry erase ink among school teachers - Ibramsah, Ainul Basirah (2022)
Objective: To evaluate the effect of dry-erase ink marker usage among school teachers towards the dry eye disease parameters including tear film breakup time (TBUT), Schirmer test and ocular surface disease index(OSDI) score. Design: A cross-sectional study was conducted from June 2020 to December 2021 involving 116 school teachers and 145 control subjects. Assessment include demographic data, average of hours of teaching in a day and a week for school teachers, TBUT test, Schirmer test and OSDI score among school teachers and control subjects. Dry eye disease was defined as OSDI score more than 12, and either TBUT less than ten seconds or Schirmer test less than 6mm in five minutes or both. Statistical analysis was done using SPSS version 26. Results: There were 116 school teachers with mean age of 48.0 year-old and 145 control subjects with mean age of 42.0 year-old involved in this study. There was statistically significant difference of OSDI score and TBUT results among school teachers compared with control subjects (p<0.01). However, there was no significant difference in Schirmer test results. There was no statistically significant relationship between hours of teaching with the TBUT test (p=0.450) and Schirmer test (p=0.327). There was no significant relationship of OSDI score with the TBUT test (p=0.629) and Schirmer test (p=0.230) among school teachers or control group (p=0.225, p=0.840). Conclusion: Ocular surface integrity and tear film are not affected by usage of dry-erase ink marker among school teachers. However dry eye among school teachers can affect the quality of work and classroom learning.